KONSEP MAQASHID AL-SHARIAH SEBAGAI TEORI PEMBENTUKAN HUKUM ISLAM TAK PERNAH TUNTAS PERSPEKTIF JASSER AUDA - Mukhlishi, Mukhlishi (Universitas Islam Madura, 2014)
The concept of maqasid al - Sharia is a basic guideline for the legal establishment , although ultimately they also influenced the value of tradition, politics. In addition, maqasid al-shari'a also plays an important role in understanding the various sources of law such as the Qur'an, Sunnah, ijma, qiyas and others. Therefore, the validity of any results of ijtihad was dependent on the level of achievement of maqasid al - Shariah .As a doctrine, maqashid as-Shari'ah intends reached, guarantees, and preserve prospirityto mankind, especially Muslims. To that end, the priority scale provided three differenciesbut complementary namely; adh-Necessities, al-Hajiyyat, and at-Tahsinat.Adh - Necessities named primary objectives as a goal to be there, that absence will result in destroying life in total.There are five interests to be protected; religion, life, intellect, property, and offspring. To save the religion, Islam requires of worship, as well as prohibit the things that ruin it. To save lives, Islam requires mankind to eat according to need. To save sense, Islam requires good attitudes among others, at the same level, it forbids damaging things like liquor sense. To save the property, Islam requires to be good to the others, as well as mu'amalah laws prohibiting measures that would ruin it like theft and robbery. To save descent, Islam regulates marriage and prohibits marriage. These efforts with one another interrelated. Effort to protect religion means also protecting reasonable efforts, possessions, and heredity.